An enzyme-like imprinted-polymer reactor with segregated quantum confinements for a tandem catalyst. Issue 3 (4th January 2018) - Wei, Wenjing; Zhou, Tingting; Wu, Shuping; Shen, Xiaojuan; Zhu, Maiyong; Li, Songjun
Abstract : This study was aimed at addressing the present challenge in tandem catalysts: how to furnish catalysts with tandem catalytic-ability without involving the precise control and man-made isolation of different types of catalytic sites. Abstract : This study was aimed at addressing the present challenge in tandem catalysts, as to how to furnish catalysts with tandem catalytic-ability without involving the precise control and man-made isolation of different types of catalytic sites. This objective was realized by constructing an enzyme-like imprinted-polymer reactor made of a unique polymer composite inspired from the compartmentalization of cells, a composite of a reactive imprinted polymer (containing acidic catalytic sites), and encapsulated metal nanoparticles (acting as catalytic reduction sites). The compilation of two types of catalytic sites with admissible access allowed this reactor to behave like compartments of cells for enzymatic reactions and hence catalytically constituted two quantum interaction-segregated domains, which led to the occurrence of catalytic tandem processes. Unlike the reported functional reactors that run tandem catalysis by largely depending on the precise control and man-made isolation of different types of catalytic sites, tandem catalysis in this reactor run naturally with segregated quantum confinements, which does not involve the precise control and isolation of different types of catalytic sites. This protocol presents new opportunities for the development of functional catalysts for complicated chemical processes.